Multiaxial elastoplastic cyclic loading of austenitic 316L steel (Fracture and Structural Integrity, 2017)
Cyclic stress-strain response and fatigue damage character has been investigated in austenitic stainless steel 316L. Hollow cylindrical specimens have been cyclically deformed in combined tension-compression and torsion under constant strain rate condition and different constant strain and shear strain amplitudes. In-phase and 90° out-of-phase cyclic straining was applied and the stress response has been monitored. Cyclic hardening/softening curves were assessed in both channels. Cyclic softening followed for higher strain amplitudes by long-term cyclic hardening was observed. Cyclic stress-strain curves were determined. Study of the surface damage in fractured specimens revealed the types and directions of principal cracks and the sources of fatigue crack initiation in slip bands.
Keywords: Multiaxial cyclic loading; 316L steel; Cyclic stress-strain curve; Crack initiation